Grey Literature Citations by Social Science Researchers in India: A Study (LIS TODAY, 2024)
Grey literature has a pivotal role in the research study. It offers valuable  insights that are often overlooked in traditional academic publications. Non conventional published materials such as reports, theses, and conference  proceedings are examples of grey literature. This study investigates the  utilization of grey literature by social science students in India, and the  findings reveal that it is widely utilized due to its accessibility, relevance to  local contexts, and provision of current information. The recent publication of  grey literature is used more than the earlier published literature. Researchers  frequently rely on government reports and NGO publications. This study  encourages researchers to cite grey literature in their research.
Keywords: Grey literature; Citation analysis; Information utilization; Unpublished Research; Social sciences; Academic resources; Accessibility